Education for UN Sustainable Development Goal 12: A Cross-Curricular Program for Secondary Level Students - Kiely, Lisa; Parajuly, Keshav; Green, James A.; Fitzpatrick, Colin (Frontiers in Sustainability, 2021)
Dealing with complex sustainability challenges requires an integrated approach to thinking and hence learning. Well-designed, integrated sustainability educational programs at the school level can have a significant positive impact on sensitizing students in this area. We present the case of a cross-curricular educational program designed and implemented at secondary level school with a focus on sustainability of material resources used in electronic products – a fast-growing sector with a significant environmental footprint. Over a four-week period, teachers of five subjects (science, geography, business, technology and civics, and society & political education) tailored their classes to focus on the topic of critical raw materials as it relates to these subjects. Examining a control group against the intervention group before and after the program, we use the New Ecological Paradigm (NEP) scale as a measure of students’ environmental beliefs in order to find out the extent to which the program helped the cohort of students develop and retain such an ecological paradigm. Students’ pro-NEP improved after the program, including on several facets, such as belief in limits to growth. Findings suggest that our cross-curricular approach was able to influence the young students’ environmental orientation in a desirable direction.